Guide de gestion des dunes et des plages associées - Gouguet , Loïc (éditions Quae, 2018)
This practical guide benefits from the experience of several authors and experts in managing coastal dune environments and in preventing natural risks. It presents useful tools in resolving problems of daily dune management.